'Africa Needs Many Lawyers Trained for the Need of their Peoples': Struggles over Legal Education in Kwame Nkrumah's Ghana. Issue 2 (21st April 2019) - Harrington, John; Manji, Ambreena
Abstract: In the late 1950s and early 1960s, the setting up of university law schools in many African nations led to often bitter battles over the purpose of legal education. The stakes in these struggles were high. Deliberately neglected under colonial rule, legal education was an important focus for the leaders of new states, including Kwame Nkrumah, first President of Ghana. It was also a significant focus for expatriate British scholars and American foundations, seeking to shape the development of new universities in Africa. Disputes centred on whether training would have a wholly academic basis, and be taught exclusively in the University of Ghana, or be provided in addition through a dedicated law school with a more practical ethos. This debate became entangled in a wider confrontation over academic freedom between Nkrumah's increasing authoritarian government and the university, with its significant body of expatriate lecturers, and indeed in wider political and class struggles in Ghana as a whole. Tensions came to a head in the period between 1962 and 1964 when the American Dean of Law was deported along with other staff on the foot of allegations of their seditious intent. In this paper we document these complex struggles, identifying the broader political stakes within them, picking out the main, rival philosophies of legal education which animated them, and relating all of these to the broader historical conjuncture of decolonisation. Drawing on a review of archival materials from the time, published histories and memoirs, as well as interviews, we aim to show that debates over legal education had a significance going beyond the confines of the Law Faculty. They engaged questions of African nationalism, development and social progress, the ambivalent legacy of British rule and the growing influence of the United States in these territories.